2008
DOI: 10.1177/014860710803200128
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Glutamine During Active Shock Resuscitation Is Safe and Enhances Tolerance of Enteral Feeding

Abstract: Enteral glutamine administered during active shock resuscitation and through the early postinjury period is safe and enhances gastrointestinal tolerance. A large clinical trial is warranted to determine if enteral glutamine administered to the hemodynamically unstable patient can reduce infectious morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 39 publications
0
25
1
5
Order By: Relevance
“…High-dose glutamine Conejero et al (13) Estivariz et al (16) Fuentes-Orozco et al (17) Garrel et al (19) Goeters et al (20) Houdijk et al (23) McQuiggan et al (29) Schulman et al (39) Subtotal (95 % CI) Total events: 44 (treatment), 60 (control) Test for heterogeneity: χ 2 16·1, df 7 (P=0·02), I 2 56·6 % Test for overall effect: Z 1·90 (P=0·06)…”
Section: Discussionmentioning
confidence: 99%
“…High-dose glutamine Conejero et al (13) Estivariz et al (16) Fuentes-Orozco et al (17) Garrel et al (19) Goeters et al (20) Houdijk et al (23) McQuiggan et al (29) Schulman et al (39) Subtotal (95 % CI) Total events: 44 (treatment), 60 (control) Test for heterogeneity: χ 2 16·1, df 7 (P=0·02), I 2 56·6 % Test for overall effect: Z 1·90 (P=0·06)…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to a relatively well-preserved enteral tolerance in patients with trauma and burns, while in patients with severe sepsis or septic shock, intolerance to enteral route for nutrition provision is a common finding. Moreover, a pilot prospective randomized trial showed improved gastrointestinal tolerance when glutamine was added to enteral nutrition in severe trauma patients during shock resuscitation [36]. …”
Section: When Is Extra Glutamine Necessary and What For?mentioning
confidence: 99%
“…Additionally, clinical studies have demonstrated that enteral glutamine administered to trauma, burn, and critically ill patients decreases morbidity in most but not all studies (3,17,19,23,42,64). We have shown that the early use of glutamine during active shock resuscitation is safe (37). Lastly, the REDOX trial includes enteral glutamine administration to critically ill patients in shock, and preliminary results appear promising (20,21).…”
Section: Discussionmentioning
confidence: 80%